PENGEMBANGAN MODUL LAYANAN APLIKASI XTRAORDINARY TUTOR BERBASIS WEBSITE - Thalia Lively; Marlina; Arianti (STMIK KHARISMA Makassar, 2023)
Xtraordinary Tutor is a website-based online private tutor search application for children with special needs in Makassar. Based on the results of data collection using a questionnaire with a total of 83 respondents, it was found that this application has not been able to choose a tutor according to the category of children with special needs. From the results of the questionnaires that have been distributed, as many as 83% of users who want a development on the tutor list to make it easier for users to find tutors according to their needs so that the authors develop applications by adding category and rating filters. This category is needed to select a tutor based on the required category while the rating is useful for assessing tutors, the user can give a rating to the tutor they have hired after the service rental ends. After implementing the development of the module, the authors distributed questionnaires to measure customer satisfaction, tested data validity and data reliability using SPSS 20, the results of the validity test and reliability test results were 83% of the users were satisfied with the addition of the tutor category which made it easier for them to choose the best tutor category. according to the needs of the child.